THE PALEOGENE REFERENCE SECTION OF THE KRIL'ON PENINSULA (THE KITOSIYA RIVER, SOUTHERN SAKHALIN) - Fot'yanova L.I.; Serova M.Ya.; Gal'versen V.G.; Zharov A.E.; Grokhotova N.M.; Tuzov V.P. (My University, 2001)
The article presents results of investigations of the Paleogene section at the Kitosiya River (the Kril'on Peninsula, southern Sakhalin). The section is proposed to be the reference one for the Kril'on subzone of the Southern structural-facies zone of the West Sakhalin depression originated in the Palcogene time. Lithological-facies peculiarities of the section are characterized, and lists of identified foraminifers, mollusks, plant imprints, spores and pollen are presented. The Kitosiya River section exhibits the lower Paleocene, middle-upper Eocene and Oligocene deposits. Stratigraphic units of the section are correlative to those of the Ishikari and Kushiro coal basins of the Honshu Island of Japan. Some formations are dated more accurately. After investigation of foraminifers, analogues of the Sinegorka Beds of the Dolinsk area are recognized for the first time at the base of the Paleogene section. The term "Snezhinka Formation" is shown to be preferable for the continental coal-bearing deposits of the Southern structural-facies zone. A stratigraphic hiatus is suspected at the Paleocene-Eocene boundary level.
Keywords: Paleogene; Kitosiya River; Sakhalin; Cenozoic::Paleogene; Кайнозой::Палеоген